Avaliação in vitro do canal cavo-interradicular em molares inferior - Harb, Leandro José Corrêa (2009)
Every endodontic treatment may lead to failures due to internal anatomical changes. Among these faults is the which links pulp chamber floor with the periodontium in the furcation area. So the purpose of this study was to evaluate the presence of this canal in 360 human permanent mandibular molars which were kept dehydrated, using four evaluation methods: radiography, naked eye (NE), dental microscope (DM) and clearing technique. The used methods (radiography and clearing) were compared to verify the presence of the furcation canal, and observed the presence of foramina through the methods (NE and DM) by the pulp chamber floor and by the furcation; as well they were compared to the results between the complete rhizogenesis groups and the incomplete ones. Three hundred and sixty mandibular molars were used that belong to the collection of the Dental Anatomy Course of the Morphology Department of UFSM, all of them with an intact pulp chamber floor and stored in dry containers. They were rehydrated, sectioned to 1,5 mm apically to the furcation and up to 0.5 mm of pulp chamber floor. After that, they were immersed in 1% sodium hypochlorite (24 hours), rinsed under running water and immersed again in 1% sodium hypochlorite in ultrasonic (10 minutes) followed by another rinsed under running water and dried at room temperature. Then they were stored individually in glass containers, numbered and capped. All evaluations were made by the one observer, being the radiography evaluation with for four samples radiographed on each piece of film with a magnifying glass (4x); the NE and DM (30x) with directional lighting in the sample; and clearing technique each sample in its container with liquid on a X-ray box and with the aid of DM (30x). Through the radiography analysis the furcation canal wasn't clear, but as a slightly radiolucent area in the furcation region in 9,04% of the samples, suspecting its presence in 2,33% and it was not found in 88,63%; through the clearing technique the canal was not found in 100%;to the NE were evident foramina in 20,9% of the furcation and 1,9% in the pulp chamber floor; through DM, 62,1% in the furcation and 5% in the pulp chamber floor. The RC group presented foramina in 61,1% in the furcation and 5,8% in the pulp chamber floor; the RI group with 64,7% in the furcation and 3% in the pulp chamber floor. Given the developed conditions in this work it's possible to conclude that radiographic evaluation really does not work as an effective means of diagnosis, but as an aid exam, important to schedule medical procedures. Observing the assessments by the NE and DM, the foramina number is much higher in the furcation than in the pulp chamber floor and can be sites of deposition of dental plaque, making cleaning more difficult in the area when exposed in the oral cavity, and there was no foramina incomplete rhizogenesis group, the use of dental microscope is an excellent tool for the visualization of dental anatomical details; the clearing technique is an excellent evaluation method, since we have the full three-dimensional visualization of internal dental anatomy, and there is a need of studying more about the use of stored dehydrated teeth in some of the methods of research.